2015
DOI: 10.1051/0004-6361/201425236
|View full text |Cite
|
Sign up to set email alerts
|

Seismic sensitivity to sub-surface solar activity from 18 yr of GOLF/SoHO observations

Abstract: Solar activity has significantly changed over the last two Schwabe cycles. After a long and deep minimum at the end of Cycle 23, the weaker activity of Cycle 24 contrasts with the previous cycles. In this work, the response of the solar acoustic oscillations to solar activity is used in order to provide insights into the structural and magnetic changes in the sub-surface layers of the Sun during this on-going unusual period of low activity. We analyze 18 yr of continuous observations of the solar acoustic osci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 51 publications
5
61
0
Order By: Relevance
“…It can be shown that the changes between cycle 22 and 23 must occur above 2400km [26]. Salabert et al [27] showed a similar result can be obtained using GOLF data.…”
Section: Cycle-to-cycle Variationsmentioning
confidence: 53%
“…It can be shown that the changes between cycle 22 and 23 must occur above 2400km [26]. Salabert et al [27] showed a similar result can be obtained using GOLF data.…”
Section: Cycle-to-cycle Variationsmentioning
confidence: 53%
“…The frequencies of solar acoustic oscillations also show a well-documented solar-cycle variation (see Fossat et al 1987;Salabert et al 2015). The frequency shifts can be interpreted as arising from structural changes in the sub-surface layers, such as changes in temperature (Kuhn et al 1988) or in the size of the acoustic cavity (Dziembowski & Goode 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Lefebvre et al (2009) showed that f -mode frequencies are mainly sensitive to the pressure scale height in the sub-surface layers. In a recent paper, Salabert et al (2015) analyzed eighteen A&A 595, A71 (2016) years of measurements of the GOLF experiment onboard SoHO to derive the temporal variability of the frequency shifts of the radial, dipolar, and quadrupolar modes for different frequency ranges sensitive to different layers in the solar sub-surface interior. They showed that the temporal evolution of the magnetic configuration imprints on these modes in a different way during cycle 23 and the weak on-going cycle 24.…”
Section: Introductionmentioning
confidence: 99%
“…The modes at higher frequencies show frequency shifts 30% smaller during Cycle 24, which is in agreement with the decrease observed in the surface activity between Cycles 23 and 24. The frequency tables associated with the work described in [57] are now available at the SPACEINN portal 7 . A total of 69 non-independent one-year frequency ta-bles of modes =0, 1, 2, and 3 are available.…”
Section: Comparison Of Solar Magnetic Activity Cycles 23-24mentioning
confidence: 99%